Update on Treatment and Prevention of Chronic Antibody Mediated Rejection in Renal Transplant Recipients (Pakistan Journal of Kidney Diseases, 2021)
Chronic antibody mediated rejection (AMR) is a major cause of allograft failure1,2. Chronic AMR clinically presents with proteinuria and gradual decline in renal function. The underlying mechanisms of AMR include both antibody mediated complement-dependent cytotoxicity, complement-independent cellular cytotoxicity and other mechanisms. The purpose of this review is to appraise recent literature on diagnosis, treatment and prevention of chronic AMR.